Opportunities for using in silico‐based extended dosing regimens for monoclonal antibody immune checkpoint inhibitors. Issue 9 (11th June 2020) - Peer, Cody J.; Goldstein, Daniel A.; Goodell, Jennifer C.; Nguyen, Ryan; Figg, William D.; Ratain, Mark J.
Abstract : Therapeutic drug monitoring (TDM) involves frequent measurements of drug concentrations to ensure levels remain within a therapeutic window, and it is especially useful for drugs with narrow therapeutic indices or extensive interindividual pharmacokinetic variability. This technique has never been applied to immuno‐oncology drugs, but, given recent examinations of clinical data (both exposure and response) on a number of these drugs, further investigations into TDM may be justified to reduce costs as well as potentially reducing the severity and/or duration of immune‐related adverse events. Specifically, all but one of the approved PD‐1 and PD‐L1 inhibitors (pembrolizumab, nivolumab, cemiplimab‐rwlc, atezolizumab, avelumab, durvalumab) have been shown to exhibit a plateaued exposure‐response (E‐R) curve at doses evaluated extensively to date, as well as time‐dependent changes in drug exposure. Furthermore, responders have a greater decrease in drug clearance over time and would, therefore, have supratherapeutic serum concentrations. With frequent trough measurements, it is possible to use pharmacokinetic modelling and simulation to estimate drug clearance via Bayesian methods. Based on patient‐specific estimates for clearance, optimal alternative dosing strategies can be simulated to lower drug and cost burden yet maintain therapeutic levels, especially as the clearance of the drug decreases over time. This review will comprehensively discuss each of the FDA approved PD‐1, PD‐L1/2 and CTLA‐4 inhibitors regarding their indications and current recommended dosing, with evidence supporting the investigation of these types of TDM strategies.